Genome-Wide Identification and Characterization of Small Peptides in Maize - Liang, Yan; Zhu, Wanchao; Chen, Sijia; Qian, Jia; Li, Lin (Frontiers in Plant Science, 2021)
Small peptides (sPeptides), less than 100 amino acids long, are encoded by small open reading frames (sORFs) often found in the 5′ and 3′ untranslated regions (or other parts) of mRNAs, in long non-coding RNAs, or in transcripts from introns and intergenic regions; various sPeptides play important roles in multiple biological processes. Here, we conducted a comprehensive study of maize (Zea mays) sPeptides using mRNA sequencing, ribosome profiling (Ribo-seq), and mass spectrometry (MS) on six tissues (each with at least two replicates). To identify maize sORFs and sPeptides from these data, we set up a robust bioinformatics pipeline and performed a genome-wide scan. This scan uncovered 9,388 sORFs encoding peptides of 2–100 amino acids. These sORFs showed distinct genomic features, such as different Kozak region sequences, higher specificity of translation, and high translational efficiency, compared with the canonical protein-coding genes. Furthermore, our MS data verified 2,695 sPeptides. These sPeptides perfectly discriminated all the tissues and were highly associated with their parental genes. Interestingly, the parental genes of sPeptides were significantly enriched in multiple functional gene ontology terms related to abiotic stress and development, suggesting potential roles of sPeptides in the regulation of their parental genes. Altogether, our study lays out guidelines for genome-wide scans of sORFs and sPeptides in plants by integrating Ribo-seq and MS data, provides a more comprehensive resource of functional sPeptides in maize, and gives us a new perspective on the complex biological systems of plants.